The clover curse - Green, Poppy; Bell, Jennifer (Jennifer A.), 1977- (New York : Little Simon, 2016)
Sophie finds a four-leaf clover that isn't exactly lucky in the seventh book of The Adventures of Sophie Mouse! Sophie Mouse is painting in Clio's Clover patch on a beautiful spring day when she spots something unusual. It's a clover ... but it has four leaves! Four-leaf clovers are supposed to bring good luck, right? Sophie waits and waits for this good luck, but it seems like just the opposite is happening. She spills paint all over herself, she doesn't have any fun daydreams, and she forgets about an adventure she was supposed to go on with Hattie! Will Sophie ever be able to break this Clover Curse? With easy-to-read language and illustrations on almost every page, the Adventures of Sophie Mouse chapter books are perfect for beginning readers.
Ages 5-9.
Keywords: Clover -- Juvenile fiction; Blessing and cursing -- Juvenile fiction; Mice -- Juvenile fiction; Frogs -- Juvenile fiction; Squirrels -- Juvenile fiction; Animals -- Juvenile fiction; Action and adventure fiction